The role of TNF-α in the pathogenesis of type 1 diabetes in the nonobese diabetic mouse: Analysis of dendritic cell maturation - Lee, Li-Fen (National Academy of Sciences, 2005)
TNF-α has been linked to the development of type 1 diabetes (T1D). We previously reported that neonatal treatment of nonobese diabetic (NOD) mice with TNF-α accelerated the onset of T1D, whereas TNF-α blockade in the same time period resulted in a complete absence of diabetes. The mechanisms by which TNF-α modulates development of T1D in NOD mice remain unclear. Here we tested the effects of TNF-α on the maturation of dendritic cells (DCs) in the NOD mouse. We found that neonatal treatment with TNF-α caused an increase in expression of maturation markers on CD11c(+)CD11b(+) DC subpopulations, whereas treatment with anti-TNF-α resulted in a decrease in expression of maturation markers in the CD11c(+)CD11b(+) subset. Moreover, neonatal treatment with TNF-α resulted in skewed development of a CD8α(+)CD11b(-)CD11c(+) DC subset such that TNF-α decreases the CD8α(+)CD11c(+) DC subset, increases the CD11c(+)CD11b(+) subset, and causes an increase in the expression of CD40 and CD54 on mature DCs capable of inducing immunity. Anti-TNF-α-treated mice had an increase in the CD8α(+)CD11c(+) DCs. Notably, adoptively transferred naïve CD4(+) T cells from BDC2.5 T cell receptor transgenic mice proliferated in the pancreatic lymph nodes in TNF-α-treated NOD mice but not in anti-TNF-α-treated mice. Finally, we show that anti-TNF-α-treated mice showed immunological tolerance to islet cell proteins. We conclude that TNF-α plays an important role in the initiation of T1D in the NOD mouse by regulating the maturation of DCs and, thus, the activation of islet-specific pancreatic lymph node T cells.